2018
DOI: 10.1021/acs.langmuir.8b00575
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Properties of Freestanding Hydrophobin Bilayers

Abstract: Hydrophobins are a family of small-sized proteins featuring a distinct hydrophobic patch on the protein's surface, rendering them amphiphilic. This particularity allows hydrophobins to self-assemble into monolayers at any hydrophilic/hydrophobic interface. Moreover, stable pure protein bilayers can be created from two interfacial hydrophobin monolayers by contacting either their hydrophobic or their hydrophilic sides. In this study, this is achieved via a microfluidic approach, in which also the bilayers' adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…A slow flow is created by hydrostatic pressure such that the lipid decorated buffer fingers are brought in close vicinity until they make a direct contact. When the two monolayers face each other, a zipping phenomenon driven by the intermolecular forces between the hydrophobic chains will occur and the bilayer will form (87). In this setup, the control of pressure and lipid concentrations is necessary to avoid rupture of the lipid bilayer (89).…”
Section: Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A slow flow is created by hydrostatic pressure such that the lipid decorated buffer fingers are brought in close vicinity until they make a direct contact. When the two monolayers face each other, a zipping phenomenon driven by the intermolecular forces between the hydrophobic chains will occur and the bilayer will form (87). In this setup, the control of pressure and lipid concentrations is necessary to avoid rupture of the lipid bilayer (89).…”
Section: Microfluidicsmentioning
confidence: 99%
“…To form a freestanding lipid membrane two microfluidic cross channel geometries previously tested as a platform to produce stable bilayers were employed (86)(87)(88). In both geometries, a continuous phase consisting of lipids dissolved in squalene solution (5 mg/mL) separates two fingers of HEPES buffer (25 mM, KCl 150 mM).…”
Section: Microfluidicsmentioning
confidence: 99%
“…The solubility of HFB layers was used for grouping HFBs in conventional classes, where class I HFBs formed insoluble functional amyloids (rodlets), while the layers of class II HFBs (which were studied here) were soluble in organic solvents and ethanol 7,11,22 . However, Winandy et al 42 showed a similar stability of layers formed on glass by HFBs from both classes, and Hähl et al 61 demonstrated the stability of HFB vesicles formed by HFB1 (class II). Therefore, we speculate that HFBs, as universal and specific fungal proteins, contribute to the formation of extracellular vesicles that attract attention in cell biology as intracellular delivery and communication vehicles 62, as demonstrated in fungi 63 , including Trichoderma 64 .…”
Section: Discussionmentioning
confidence: 99%
“…The solubility of HFB layers was used for grouping HFBs in conventional classes, where class I HFBs formed insoluble functional amyloids (rodlets), while the layers of class II HFBs (which were studied here) were soluble in organic solvents and ethanol [ 7 , 20 , 21 ]. However, Winandy et al [ 63 ] showed a similar stability of layers formed on glass by HFBs from both classes, and Hähl et al [ 65 ] demonstrated the stability of HFB vesicles formed by HFB1 (class II). Therefore, we speculate that HFBs can contribute to the formation of extracellular vesicles that attract attention in cell biology as intracellular delivery and communication vehicles [ 66 ], as demonstrated in fungi [ 67 ], including Trichoderma [ 68 ].…”
Section: Discussionmentioning
confidence: 99%